Integración de las actividades STEM en libros de texto - Ferrada Ferrada, Cristian Andres; Díaz Levicoy, Danilo Antonio; Carrillo Rosúa, Francisco Javier (Revista Fuentes, 2021)
En el siguiente trabajo se analizan las actividades, que buscan desarrollar la experimentación y potenciar las habilidades STEM, sugeridas en los libros de texto de Ciencias de Educación Primaria en España y Chile. En su análisis, se identificaron las actividades STEM y se clasificaron según el modelo de análisis de currículos integrados, que plantea seis maneras de abordar la integración de una actividad de este tipo. Posteriormente, se clasificaron según una adaptación del enfoque de perspectivas de Educación Ambiental. Los hallazgos dan cuenta de la necesidad de relacionar diversas disciplinas para lograr el desarrollo de una actividad exitosa, al igual que la necesaria conexión de conocimientos previos que poseen los estudiantes como base de nuevos aprendizajes. Resumen The STEM educational perspective is rising and it s consistent with the competence approach incorporated in educational law. The aim of this work is to analyze to what extent the Primary Education Sciences textbooks in Spain and Chile are aligned with this STEM perspective. Following a content analysis methodology, in the 12 widely disseminated analyzed textbooks, 462 activities were identified. Among them, 164 (less than 50%) are related with, at least, one STEM area. These activities were classified according to the integrated curriculum analysis model, which proposes six ways to approach the integration of an activity.The “linked approach” shows a greater relevance in Spanish (50%) and Chilean textbooks (46%). In adition, the activities were classified according to an adaptation of the environmental education perspective approach. Among 5 existing approaches, the “experiential” (60) and the “praxique” (50) are the most prevalent approaches. The findings reveal the need to increase the relationship among disciplines to achieve a truly integrated STEM approach.